Managing reputational risk at Bosch car multimedia - Portugal: creating safety nets through corporate communication programs - Salgado, Paulo Jorge Castro Faria (2015)
The renewed focus on the study of corporate reputation shows an increasing acknowledgement that this intangible asset has a strong role to play in a company’s ability to thrive. Notwithstanding, managing the reputation of an organization seems to be a difficult task, or one that is neglected by most executive managers, who fail to defend their companies from crisis situations. In this paper, our purpose is to analyze the corporate communication programs of the company Bosch Car Multimedia - Braga (Portugal) and thereby gain a deeper understanding of the role played by ‘safety nets’ in managing reputational risk and preventing crisis scenarios at a local level. In this context, we conducted a study in order to analyze the state of the art of BCMP’s corporate communication programs, which were created locally with the aim of contributing to the development of ‘safety nets’. BCMP is an interesting case for study and debate with respect to reputational risk and crisis communication, along with the development of ‘safety nets’, since the company has to face the challenge of combining a centralized communication structure (based in Germany) with a strong and demanding union workforce.